Hands-on auto DevOps with GitLab CI (Packt, 2019)
"Developing modern software requires an automated pipeline that builds, tests, and deploys your application, complete with its required infrastructure. GitLab is a Git-based version control server, available at gitlab.com or as a private server. GitLab CI provides automated builds and deployments right from within GitLab. With GitLab CI, it is easy to add build and deployment automation that triggers on every code change, helping you build high-quality, reliable software and deploy it to production at speed. This course will give you a hands-on tutorial on GitLab CI. You will use GitLab CI to create a DevOps pipeline to automatically build, test, and deploy software to virtual machines and container environments."--Resource description page